Implementation of Antibiotic Discovery by Student Crowdsourcing in the Valencian Community Through a Service Learning Strategy - Maicas, Sergi; Fouz, Belén; Figàs-Segura, Àngela; Zueco, Jesús; Rico, Hortensia; Navarro, Alfonso; Carbó, Ester; Segura-García, Jaume; Biosca, Elena G. (Frontiers in Microbiology, 2020)
Antibiotic misuse is a public health problem due to the appearance of resistant strains in almost all human pathogens, making infectious diseases more difficult to treat. The search for solutions requires the development of new antimicrobials as well as novel strategies, including increasing social awareness of the problem. The Small World Initiative (SWI) and the Tiny Earth network (TE) are citizen science programmes pursuing the discovery of new antibiotics from soil samples and the promotion of scientific culture. Both programmes aim to bring scientific culture and microbiological research closer to pre-university students through a crowdsourcing strategy and a Service Learning educational approach, with a twofold objective: to encourage students to pursue careers in science and to involve them in the discovery of soil microorganisms producing new antimicrobials. SWI and TE projects were put into practice in Spain under the common name MicroMundo. MicroMundo@Valencia was implemented at the Universitat de València (UV) during the academic years 2017-2018 and 2018-2019. It trained 140 university students to disseminate this initiative into 23 high/secondary schools, and one primary school, involving about 900 people (teachers and students) as researchers. A total of 7002 bacterial isolates were obtained from 366 soil samples and tested for antibiosis at UV and high/secondary school centers. About 1% or 7% of them produced inhibition halos for the Escherichia coli or Bacillus cereus target strains, respectively. Geolocation of sampling sites by an application developed ad hoc and Kriging analysis also allowed detection of soil foci of antibiotic-producing bacteria. Evaluation of the project by university, high/secondary and primary school students revealed their strong positive perception and their increased interest in science, as a consequence of acquiring new scientific and pedagogical concepts and skills that they were able to pass on to other classmates, younger students or relatives. To further expand the dissemination of the project in the Valencian Community, diverse extramural activities deemed to include a gender perspective and aimed at different age groups, were also carried out, obtaining very satisfactory results, increasing sensitivity and awareness to the global antibiotic crisis.